Peran Kepemimpinan Transformasional Kepala Sekolah dalam Implementasi Kurikulum Montessori untuk Membentuk Karakter Murid di Cinnamon Montessori School Jakarta - Agustin, Lydia; Tung, Khoe Yao (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2024)
The Montessori curriculum is increasingly developing in Indonesia, particularly addressing early childhood education and kindergarten. The success of the curriculum is significantly influenced by the teaching staff led by the principal. The appropriateness of the principal's leadership model is crucial for the teachers to effectively implement the Montessori curriculum for their students. The aim of this study is to explore the role of transformational leadership of a principal in initiating changes, both in teacher readiness and the ultimate outcome, which is the character formation of students, within the context of teaching and learning activities at Cinnamon Montessori School in Jakarta. The research was conducted qualitatively. Data for this study were obtained through the participation of 11 teachers, 10 parents, and 1 principal, using interview and observation techniques, and data analysis was performed using the coding method (Strauss and Corbin, 1989). The results of the study indicate that the transformational leadership role of the Principal at Cinnamon Montessori School has an impact on the character formation of students, which is acknowledged by the parents.AbstrakKurikulum Montessori semakin berkembang di Indonesia untuk menjawab khususnya pada pendidikan anak usia dini maupun TK. Keberhasilan Kurikulum tentu diperankan oleh tenaga pengajar yang dipimpin kepala sekolah. Tujuan dari penelitian ini adalah untuk mengeksplorasi peran kepemimpinan transformasional seorang kepala sekolah dalam menginisiasi perubahan, baik dalam kesiapan guru maupun hasil akhirnya, yaitu pembentukan karakter siswa, dalam konteks kegiatan belajar mengajar di Sekolah Montessori Cinnamon Jakarta. Penelitian dilakukan secara kualitatif deskriptif. Data untuk penelitian ini diperoleh melalui partisipasi 11 guru, 10 orangtua siswa, dan 1 kepala sekolah, dengan menggunakan teknik wawancara, observasi, dan analisis data dilakukan dengan metode coding (Strauss dan Corbin, 1989). Hasil penelitian menunjukkan bahwa peran kepemimpinan transformasional yang diemban oleh Kepala Sekolah di Sekolah Montessori Cinnamon memberikan dampak perubahan dalam pembentukan karakter siswa, yang diakui oleh orangtua siswa.